2017
DOI: 10.1007/s11934-017-0710-y
|View full text |Cite
|
Sign up to set email alerts
|

Training in Robotic Surgery—an Overview

Abstract: Purpose of ReviewThere has been a rapid and widespread adoption of the robotic surgical system with a lag in the development of a comprehensive training and credentialing framework. A literature search on robotic surgical training techniques and benchmarks was conducted to provide an evidence-based road map for the development of a robotic surgical skills for the novice robotic surgeon.Recent FindingsA structured training curriculum is suggested incorporating evidence-based training techniques and benchmarks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 42 publications
1
88
0
3
Order By: Relevance
“…Robotic surgery is a multidisciplinary, complex environment and, thus, requires further development of NTS alongside TS training [1,4]. New challenges include the new technology, the surgeon being physically displaced from their team, a change in the surgeons' role and additional staff members to communicate with.…”
Section: Training For Robotic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic surgery is a multidisciplinary, complex environment and, thus, requires further development of NTS alongside TS training [1,4]. New challenges include the new technology, the surgeon being physically displaced from their team, a change in the surgeons' role and additional staff members to communicate with.…”
Section: Training For Robotic Surgerymentioning
confidence: 99%
“…In the last decade, NTS have emerged as a vital area for improvement within healthcare: they are a major cause for error, causing 86% of adverse events in open surgery [3,4]. A UK-based evaluation of skills survey found that only 41% of urological trainees felt that their NTS training was sufficient for their first day of practice compared to 78% of specialists, with an even lower 25% of trainees believing their current NTS training was sufficient [5].…”
Section: Introductionmentioning
confidence: 99%
“…The field is rapidly changing with several new innovations in hardware and software [2,3]. A number of research labs that study extensions in hardware and software for surgical robots use animal tissue or synthetic proxies for tissues and anatomy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery presents great potentials towards safer, more accurate and consistent minimally invasive surgery (MIS) [1]. However, their adoption is fundamentally dependent on the access to training facilities and extensive surgical training [2,3]. Robotic instruments require different dexterity skills compared to open or laparoscopic surgery as well as across different robotic systems.…”
Section: Introductionmentioning
confidence: 99%